PENDAMPINGAN CEK FAKTA BERBASIS KOMUNITAS UNTUK MENINGKATKAN LITERASI DIGITAL PEMUDA DI SUNTER AGUNG JAKARTA UTARA - Dani Setiadarma; Mohammad Ismed; Ferdi Setiawan (Jurnal Penelitian dan Pengabdian Kepada Masyarakat UNSIQ, 2026)
The era of Society 5.0 has intensified the integration of digital technologies while also facilitating the proliferation of misinformation and hoaxes across social media platforms. The limited capacity for fact-checking has rendered communities increasingly susceptible to false narratives. In response, a community service initiative was launched to enhance the digital literacy of youth in Sunter Agung, North Jakarta, through a mentoring program focused on community-based fact-checking. This initiative engaged 25 young participants and utilized a participatory mentoring framework that included digital literacy education, hands-on practice with verification tools, case simulations, and community mentorship. The evaluation methodology comprised pre-tests, post-tests, observations, and practical assessments. Findings indicated a notable improvement in participants' proficiency with digital fact-checking tools, rising from 58% to 83%, alongside significant behavioral shifts towards verifying information prior to sharing it on social media. Additionally, the program developed a model for community-based fact-checking mentorship that holds promise for implementation in other urban settings.